Nutrient Contribution of the Dinner Meal Consumed by Low-Income Minority Preschool Children - O'Neil, Carol E.; Nicklas, Theresa A.; Hughes, Sheryl O.; Liu, Yan (International Journal of Child Health and Nutrition, 2012)
Objective: To examine the energy and nutrient intake of dinner of low income preschool minority groups, African-Americans and Mexican-Americans, attending Head Start (HS). Design: Cross-sectional study of intake at dinner using digital photography was undertaken. Pictorial records were converted to energy and nutrient intakes using NDS-R Nutritional software. Means±SE for total grams of food and beverages, energy, and macro- and micro-nutrients were determined and compared with recommendations. Setting: Home assessment dinner of children enrolled in HS in Houston, TX. Subjects: Low-income children (n=214), 3 to 5 years (mean age 4.4 ± 0.7 years; 48% boys; 53% Mexican-American). Results: Energy from food and beverages and food was 350.29±10.36 kcals and 302.35±10.46 kcals, respectively. Mean protein, carbohydrate, and total fat intakes were 14.22±0.52 g (16.32% of total energy), 44.33±1.25 g (52.24%), and 13.18±0.56 g (32.29%), respectively, which provided 95.4±0.52%, 44.5±1.25%, and 10.4±0.11% of the requirements for protein, carbohydrate, and dietary fiber, respectively; these were consistent with recommendations. Intakes of vitamin D, calcium, and potassium were 0.66±0.08 mcg, 102.61±5.03 mg, and 404.42±13.63 mg, respectively; which constituted only 6.6±0.08%, 12.7±5.03%, and 10.7±13.63% of these nutrients of public health concern. Conclusions: Children participating in HS had low intakes of nutrients of public health concern at the dinner meal. The dinner meal is an integral part of the daily intake of preschool children and this study suggests that micronutrient intakes could be improved. It is important to educate mothers and children as to what constitutes a nutrient-dense meal and to confront barriers to consumption of these meals.